2020
DOI: 10.1542/peds.2019-2482
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Testing Among Perinatally Exposed Infants

Abstract: BACKGROUND: Hepatitis C virus (HCV) prevalence doubled among pregnant women from 2009 to 2014, reaching 3.4 per 1000 births nationwide. Infants exposed to HCV may acquire HCV by vertical transmission. National guidelines recommend that infants exposed to HCV be tested; however, it is unclear if these recommendations are being followed. Our objectives were to determine if infants exposed to HCV were tested and to determine hospital-and patient-level factors associated with differences in testing. METHODS: In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 26 publications
1
46
1
Order By: Relevance
“…Data suggest, however, that only a minority of exposed infants are tested. 97,98 Because infants with opioid exposure are at risk for HCV exposure, it is imperative that (1) all infants with opioid exposure are evaluated for HCV exposure and (2) all infants with HCV exposure are adequately managed to determine if they acquire the virus. All infants HCV exposure should be evaluated and should be tested for seroconversion by using RNA polymerase chain reaction or antibody testing.…”
Section: Discharge Educationmentioning
confidence: 99%
“…Data suggest, however, that only a minority of exposed infants are tested. 97,98 Because infants with opioid exposure are at risk for HCV exposure, it is imperative that (1) all infants with opioid exposure are evaluated for HCV exposure and (2) all infants with HCV exposure are adequately managed to determine if they acquire the virus. All infants HCV exposure should be evaluated and should be tested for seroconversion by using RNA polymerase chain reaction or antibody testing.…”
Section: Discharge Educationmentioning
confidence: 99%
“…They reported successfully screening for HCV among pregnant women with opioid use. In retrospective cohort study of infants exposed to HCV who were enrolled in the Tennessee Medicaid program, testing was conducted in only 23% of infants and less frequently among African American infants[ 16 ]. These two observations indicate that infant HCV screening is currently imperfect, emphasizing the need for programmatic changes to improve both mother and infant follow-up to bridge gaps in the cascade to cure.…”
Section: Epidemiology Of Hepatitis Cmentioning
confidence: 99%
“…These infants have always been included in the risk-based screening recommendations, but plenty of studies have shown that the ultimate screening rate for these infants is abysmal. 48 , 49 , 50 Screening at birth has not been shown to be effective, and antibody-based tests cannot be used until after 18 months due to passively transferred maternal antibody. The American Association for the Study of Liver Diseases and the Infectious Diseases Society of America (AASLD-IDSA) HCV Guidance Panel endorsed 2–6 months as an age window during which the use of an HCV RNA test seemed to offer reliable results to confirm or exclude infection.…”
Section: Is Universal Screening Truly Universal? What Else Is Requirementioning
confidence: 99%